Dirāsa al-Qur’ān bi Ṭarīqa Satīlistīkiyya - Syihabuddin Q (Al-Jami'ah Research Centre, 1999)
Many people admire and interested in the Qur'ān, but they don't know the reason. According to the author, there is an internal factor that make people interested in the Qur'ān not mainly based on the dogmatic reason. The present paper discusses the so called